Adenocarcinoma arising from an anal gland—Report of a case - Sakamoto, Takashi (Elsevier, 2014)
INTRODUCTION: Adenocarcinoma arising from an anal gland is extremely rare. Most anal canal cancers are squamous cell carcinoma, and adenocarcinoma is infrequently diagnosed. Diagnostic criteria and the standard treatment for adenocarcinoma of the anal canal have not been clearly defined, in part because of the rarity of this lesion. PRESENTATION OF CASE: An 84-year-old man who presented with a piece of tissue prolapsing from the anus. An incisional biopsy showed adenocarcinoma, and an abdomino-perineal resection was then performed. Cytokeratin 7 (CK7), cytokeratin 19 (CK19) stained positive in the specimen, suggesting that the tumor developed from an anal gland. The patient was discharged after surgery without any complications. DISCUSSION: Exact diagnostic criteria for adenocarcinoma of the anal canal have not been previously described. In the present case, CK7 and CK19 were stained, and the tumor showed positivity for both of these markers, which is compatible with the staining patterns of anal gland origin cancer. Radical resection is recommended rather than local resection, because of the tumor's high recurrence rate. Some authors recommend combined modality treatment with preoperative or postoperative chemoradiotherapy because of the high rate of distant recurrence. CONCLUSION: The preoperative diagnosis of adenocarcinoma arising from an anal gland is not easily established. However, it may be possible to suspect an anal glandular adenocarcinoma based on a meticulous physical examination, appropriate diagnostic studies and pathological findings on biopsy.